Фітосанітарна оцінка форзицій (Forsythia Vahl) у зв’язку з інтродукцією в Правобережному Лісостепу України - Goncharenko, B.V.; Medin, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The data of phytosanitary inspection of forsythia (Forsythia Vahl) in plantations in Right-Bank of Forest-Steppe of Ukraine are given. Recommendations for forsythia protection from diseases and pests are developed.